Computer aided learning for metrology students / Ahmad Fhattah Syaifuddin Kamarudin - Kamarudin, Ahmad Fhattah Syaifuddin (2005)
This project is based on the laboratory experiments done by Metrology students of Faculty of Mechanical Engineering, UiTM. These experiments are selected to initiate this project i.e. Straightness Measurement, Calibration of a Dial Gauge and Angular Measurement. These experiments are transformed into virtual laboratory system using software. The software of Visual Basic 6.0 is being used for this system. The project also provides a brief overview of the programming part using Visual Basic 6.0 as one of the powerful high level programming language for the virtual laboratory system. Hence, a system has been developed to help students in their learning especially in the field of Metrology. It is hoped that the student's effective learning and their interest in study in this particular subject will increase.